PENERAPAN GAYA EKSPOSITORI DALAM FILM DOKUMENTER PENDEK “LUDRUK DI UJUNG TANDUK” - Ariesta, Rangga Bertrand; Dwiyani, Ni Kadek; Lawranta, Gangga (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
The documentary film Ludruk di Ujung Tanduk explores the declining presence and preservation efforts of Ludruk, a traditional theatrical art from East Java, especially in Surabaya. Utilizing an expository style combined with poetic nuances, the film attempts to deliver cultural values and socio-political reflections through structured narration and authentic interviews. Key figures such as Cak Kartolo and Bunda Nonik Arboyo provide firsthand insight into Ludruk’s current reality. The documentary serves as both cultural preservation and educational media, aiming to raise awareness among modern viewers, particularly youth, about the urgency of safeguarding intangible heritage amid globalization.